2020
DOI: 10.1002/art.41517
|View full text |Cite
|
Sign up to set email alerts
|

Obesity‐Related Traits and the Development of Rheumatoid Arthritis: Evidence From Genetic Data

Abstract: Objective To investigate the association between obesity‐related traits and risk of rheumatoid arthritis (RA). Methods We conducted genetic correlation analysis and a 2‐sample Mendelian randomization (MR) study, using genome‐wide genetic data based on >850,000 individuals of European ancestry. Summary statistics were collected from the largest genome‐wide association study conducted to date for body mass index (BMI; n = 806,810), waist‐to‐hip ratio (WHR; n = 697,734), WHR adjusted for BMI (WHRadjBMI; n = 694,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…The number of MR studies based on independent study samples for each disease category was two for diabetes mellitus [ 7 , 8 ], 13 for circulatory system diseases [ 9 – 21 ], three for respiratory diseases [ 8 , 22 , 23 ], six for digestive system diseases [ 24 29 ], five for musculoskeletal system diseases [ 30 34 ] plus FinnGen consortium (for osteoporosis), five for nervous system diseases [ 35 39 ], and 14 for neoplasms [ 40 – 53 ]. Among the selected studies, six studies included East-Asian (Chinese [ 11 , 25 , 42 ] and Japanese [ 48 , 50 ]) or Chilean [ 53 ] individuals, whereas the remaining studies included individuals of European ancestry or mixed (trans-ancestry) populations.…”
Section: Resultsmentioning
confidence: 99%
“…The number of MR studies based on independent study samples for each disease category was two for diabetes mellitus [ 7 , 8 ], 13 for circulatory system diseases [ 9 – 21 ], three for respiratory diseases [ 8 , 22 , 23 ], six for digestive system diseases [ 24 29 ], five for musculoskeletal system diseases [ 30 34 ] plus FinnGen consortium (for osteoporosis), five for nervous system diseases [ 35 39 ], and 14 for neoplasms [ 40 – 53 ]. Among the selected studies, six studies included East-Asian (Chinese [ 11 , 25 , 42 ] and Japanese [ 48 , 50 ]) or Chilean [ 53 ] individuals, whereas the remaining studies included individuals of European ancestry or mixed (trans-ancestry) populations.…”
Section: Resultsmentioning
confidence: 99%
“…A significant result was also observed for WHR and PCOS ( r g =0.32, P =1.34×10 −10 ). Given the complex interplay between BMI and WHR [ 29 ], we continued to investigate WHR ad jBMI, a residual component of WHR in which the effect of BMI was removed. Perhaps not surprisingly, when the effect of BMI was removed from WHR (WHR adj BMI), the prior positive genetic correlation between PCOS and WHR was attenuated to null (WHR adj BMI: r g =0.09, P =0.04).…”
Section: Resultsmentioning
confidence: 99%
“…An MR study demonstrated that a one-year delay in age at menarche reduced adult BMI by 0.38kg/m 2 (95%CI 0.25-0.51kg/m 2 ). [25] Global adiposity is a robust causal risk factor for RA as demonstrated by our recently published MR. [26] It is likely that traditional epidemiological investigations did not adequately control for the confounding effects from obesity. The protective effect of education on RA has been reported by observational studies.…”
Section: Discussionmentioning
confidence: 99%